Streamflow variability and its linkage to ENSO events in the Ethiopian Rift Valley Lakes Basin - Worako, A. W.; Haile, Alemseged Tamiru; Taye, Meron Teferi (Elsevier, 2021)
Study Region: The Ethiopian Rift Valley Lakes basin is found in the main Ethiopian Rift Valley system. Study Focus: Understanding the hydrological impact of El Niño-Southern Oscillation (ENSO) is of a paramount importance for society since it substantially affects the environmental and socio-economic conditions. The relation between ENSO indicators (SOI, MEI and Niño3.4) and streamflow magnitude was statistically evaluated with partial correlation, cross correlation, extreme streamflow indices and streamflow deficits to provide empirical evidence on how ENSO phases (La Niña and El Niño) affect streamflow variability. Trends of streamflow and ENSO indicators were tested using the non-parametric Mann-Kendall test. New Hydrological Insights for the Region: Our findings indicate that the partial correlation between the catchment area and ENSO effect on streamflow were not statistically significant at p < 0.05 after removing the south-north gradient. The direction of the ENSO effect is spatially inconsistent since El Niño (La Niña) causes positive deviation in some catchments and negative deviation for other catchments. Though statistically insignificant, reduced flow is detected for many catchments during El Niño years. For most catchment, the extreme high flow has a larger magnitude during La Niña than El Niño whereas the extreme low flow has a larger magnitude during El Niño than La Niña years. Overall, the relationship between ENSO and streamflow of the study area is found spatially inconsistent and statistically insignificant for most catchments.